Improving Creative Thinking Skills and Learning Independence in Vocational High School Students through STEM-Integrated Project-Based Learning Models - Sudiyarti Sudiyarti; Budi Pratikno; Adi Suryanto (Universitas Negeri Semarang, 2026)
Background – Improving vocational high school students’ creative thinking skills and learning independence is important to meet modern industry demands, requiring innovative approaches such as STEM-integrated Project-Based Learning (PjBL) that engage students in problem-solving and real-world projects. Purpose - This study aims to analyze the application of the STEM-integrated PjBL model in improving students’ creative thinking skills and learning independence. Method/approach - This study used a quantitative approach with a quasi-experimental non-equivalent control group design involving pretest and posttest. The population consisted of grade XI vocational high school students in Purbalingga, Central Java. The sample was selected purposively from grade XI TKJ students at SMK N 1 Purbalingga and SMK N 1 Kemangkon. Data were collected through creative thinking tests, learning independence questionnaires, and observation sheets. Instrument validity was tested by comparing the calculated r-value with the r-table value (0.3809), and reliability was measured using Cronbach’s alpha. Findings - Several test items were declared valid, and the learning independence questionnaire showed factor loadings between 0.720–0.756. Reliability results showed Cronbach’s alpha values of 0.74 for the creative thinking instrument and 0.773 for the learning independence questionnaire. Conclusions - The N-Gain results showed that students’ creative thinking skills improved more in the experimental class than in the control class. However, the increase in learning independence was minimal and showed no significant difference between the two groups.